THE POTENTIAL OF BUTTERFLY PEA FLOWER (Clitoria ternatea) AS AN ANTIBACTERIAL AGAINST Escherichia coli BY IN VITRO - Andyanita Hanif Hermawati; Aesthetica , Aesthetica Islamy (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
Abstract. The prevalence of Escherichia coli resistance in Indonesia to antibiotics is 43%. This is a serious problem because it can reduce the efficiency and effectiveness of treatment. Therefore, new products with high antibiotic potential are needed, one of which is telang flower. Telang flowers have active substances with the ability to inhibit bacterial activity. This study aims to test the antibacterial potential of telang flower (Clitoria ternatea) by maceration using 96% ethanol solvent. The research design was an experiment with a control group. The antibacterial testing method used was the agar diffusion method with three repetitions. The telang flower (Clitoria ternatea) extracts used were 50% and 100%. Data were obtained in the form of inhibition zone diameter data. The data were analyzed univariately and bivariate, namely comparing the diameter of the inhibition zone produced from each concentration with the diameter of the inhibition zone of positive and negative controls and bivariate using ANOVA. The results of this study showed that the average diameter of the inhibition zone produced was 15.28 mm (50% concentration) and 19.68 mm (100% concentration). The results of the bivariate analysis showed a p-value = 0.000. This indicates that there is a difference in the diameter of the inhibition zone in all treatment groups. The recommendation from the results of this study is that telang flower extract (Clitoria ternatea) can be continued in vivo research to identify its potential as an alternative antibacterial drug. Keywords: antibacterial; antibiotic; butterfly pea flower; herbal